Business Law Service in the Workplace as a Career Trend or To Wage Erosion - Minimum Wage - Naumovski, Ljupcho (International Journal of Law and Public Policy (IJLAPP), 2021)
The research motivated by the importance of the minimum wage, and to make the relevance of this paper based on inconsistencies in the equality of legal regulation of the minimum wage. The purpose of the research is an overview of CEEC in the economic field/relations regarding the current demand for the minimum wage to the workplace. Methodology used are the dialectical method with the methods of formal-logical, system-structural, comparative legal and statistical analysis through the study of monographs, scientific literature, analysis of existing laws and regulations, data synthesis. Based on this research concluded that the importance of the level of payment, but not the inadmissibility of determining a payment less than the minimum wage. However, for the minimum wage to fulfil its economic, social and legal function today, it must be set at a sufficiently appropriate level.